2.9k views
4 votes
Use the pair of functions to find f(g(x)) and g(f(x)). Simplify your answers. F(X)=sqrt x+8, g(x)=x^2+3

1 Answer

5 votes

Recall that:


\begin{gathered} f(g(x))=f(x^2+3), \\ g(f(x))=g(√(x)+8). \end{gathered}

Evaluating the functions, we get:


\begin{gathered} f(g(x))=√(x^2+3)+8, \\ g(f(x))=(√(x)+8)^2+3. \end{gathered}

Simplifying the second function, we get:


g(f(x))=x+16√(x)+64+3=x+16√(x)+67.

Answer:


\begin{gathered} f(g(x))=√(x^2+3)+8, \\ g(f(x))=x+16√(x)+67. \end{gathered}

User CurlyBraces
by
6.2k points